2022
DOI: 10.1002/agj2.21036
|View full text |Cite
|
Sign up to set email alerts
|

Barley yield and malt characteristics as affected by nitrogen and final irrigation timing

Abstract: Idaho is a major malt barley (Hordeum vulgare L.) producer in the United States. Production is concentrated in the semi‐arid Snake River Plain region of southern Idaho. Irrigation and fertilizer N applications are two of the most important managed factors. Research was conducted at the University of Idaho Kimberly Research & Extension Center near Kimberly, ID, to determine yield, grain quality, and malt characteristics as affected by N application rate (0, 56, 112, and 168 kg N ha−1) and final irrigation timin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…However, barley production in the semiarid west is concentrated in high‐value malting barley, where yields are typically large and strict quality specifications must be met. Research has shown that barley grain quality can be decreased, particularly when the water deficit occurs during grain formation (Carter & Stoker, 1985; Qureshi & Neibling, 2009; Rogers et al., 2022). Of major interest to the end‐product of malt and beer production is the end protein levels that are critical for the malting process.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, barley production in the semiarid west is concentrated in high‐value malting barley, where yields are typically large and strict quality specifications must be met. Research has shown that barley grain quality can be decreased, particularly when the water deficit occurs during grain formation (Carter & Stoker, 1985; Qureshi & Neibling, 2009; Rogers et al., 2022). Of major interest to the end‐product of malt and beer production is the end protein levels that are critical for the malting process.…”
Section: Resultsmentioning
confidence: 99%
“…DP increased and was within the acceptable target for adjunct brewing at all irrigation levels but was only within the target range at 100% ET c for all‐malt brewing. Free amino N is generally considered to increase with greater overall grain protein content (Luo et al., 2019; Rogers et al., 2022). However, despite an increase in grain protein/N with decreased irrigation, no irrigation effect was measured from FAN and only genotype differences were measured.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Termination of irrigation at Feekes 10.0 is considered water stressed, and termination of irrigation at F11.2 and +77F11.2 is considered well watered. Water‐stressed conditions in the F10.0 treatment resulted in a more than 30% reduction in grain yields, and N fertilizer provided little benefit to a net negative effect under water‐stressed conditions (Figure 1; Rogers et al, 2022). Maximum yield in the study occurred well below the maximum rates of fertilizer N applications for both F11.2 and +7F11.2, which did not differ.…”
Section: Yield Responsementioning
confidence: 99%